An evaluation of the potential use of Cryptosporidium species as agents for deliberate release. Issue 4 (3rd December 2013) - Hagen, Ralf Matthias; Loderstaedt, U; Frickmann, H
Abstract : Introduction: We evaluated the potential of Cryptosporidium spp. for intentional transmission as a terrorist tactic in asymmetric conflicts in terms of the recognised optimum conditions for biological warfare. Methods: Published and widely accepted criteria regarding the optimum conditions for the success of biological warfare based on experience from passive biological warfare research were applied to hypothetical intentional Cryptosporidium spp. transmission. Result: The feasibility of the use of Cryptosporidium spp. transmission for terrorist purposes was established. Particularly on tropical deployments with poor hygiene conditions, such attacks might have a good chance of remaining undetected as a deliberate terrorist attack. Conclusions: Intentional transmission should be suspected in cases of sudden outbreaks of cryptosporidiosis, particularly where adequate food and drinking water hygiene precautions are being enforced. Appropriate diagnostic procedures should be available so that the diagnosis is not missed.